2019
DOI: 10.20546/ijcmas.2019.802.152
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sweet Corn Hybrid to Establishment Methods and Weed Management Practices under Temperate Conditions

Abstract: A field experiment on "Response of Sweet corn hybrid to establishment methods and weed management practices under temperate conditions" was conducted at research farm of Faculty of Agriculture (SKUAST-K) kharif during 2017. The treatments comprised of three establishment methods (Transplanting polypot (TP),Transplanting nursery (TN) and Direct Seeding (DS) and six weed management practices (Atrazine @ 1.5 kg a.i. ha -1 as pre emergence + hand weeding and intercultivation at 30 days after sowing (W1), Pendimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 8 publications
(5 reference statements)
11
4
0
Order By: Relevance
“…Triveni et al (2017) reported that significantly maximum plant height was found in hand weeding twice at 20 and 40 DAS. Similar results were also revealed by Barad et al (2016) and Fayaz et al (2019).…”
Section: Plant Heightsupporting
confidence: 91%
“…Triveni et al (2017) reported that significantly maximum plant height was found in hand weeding twice at 20 and 40 DAS. Similar results were also revealed by Barad et al (2016) and Fayaz et al (2019).…”
Section: Plant Heightsupporting
confidence: 91%
“…For instances, high germination percentage from sowing sweet corn seeds in plastic plug trays and consequently good field performance were observed by [35,36,37]. Fayaz et al [32] experienced enhancements of germination percentage, leaf number, root and shoot lengths, seedlings fresh and dry weights and vigour index of sweet corn under controlled temperature in transplanted poly pot. Rattin et al [30] and Di Benedetto et al [38] also reported greater germination or emergence of maize by transplanting as compared to direct sowing in main field.…”
Section: Superior Seed Quality Parametersmentioning
confidence: 99%
“…Transplanting of maize assures high crop stand establishment as chances of seedling mortality is comparatively less than direct seeded maize due to choosing healthy seedlings for transplanting [30,31,32]. Further, transplanting requires less seed rate to produce optimum plant population than direct sowing.…”
Section: Better Stand Establishmentmentioning
confidence: 99%
“…Hand weeding is also difficult to achieve in large tracts of land. It is also difficult to eradicate underground reproductive parts of the weeds, hence not very effective [19].…”
Section: Introductionmentioning
confidence: 99%